2021
DOI: 10.1039/d1ra04300e
|View full text |Cite
|
Sign up to set email alerts
|

A rapid analysis of antioxidants in Sanghuangporus baumii by online extraction-HPLC-ABTS

Abstract: Rapid discovery of antioxidants from natural product by online OLE-HPLC-ABTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Owing to the fact that the chromatogram of the second extraction was stable and no residual peak was detected ( Figure 2 (C)), it was shown that the sample could be completely extracted in the first online extraction. The high extraction efficiency could be attributed to the high pressure of the OLME system, which allows better access of the mobile phase inside the matrix and ensures better extraction [ 17 , 18 ]. The method is green and efficient, with minimal sample consumption, and can be easily applied to the analysis of natural products or other solid materials, especially for those samples that are difficult to obtain or more valuable.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the fact that the chromatogram of the second extraction was stable and no residual peak was detected ( Figure 2 (C)), it was shown that the sample could be completely extracted in the first online extraction. The high extraction efficiency could be attributed to the high pressure of the OLME system, which allows better access of the mobile phase inside the matrix and ensures better extraction [ 17 , 18 ]. The method is green and efficient, with minimal sample consumption, and can be easily applied to the analysis of natural products or other solid materials, especially for those samples that are difficult to obtain or more valuable.…”
Section: Resultsmentioning
confidence: 99%
“…However, ethanol extracts also contain other components, such as sesquiterpenoids and carbonyl compounds’ derivatives, suggesting that compounds in the Sanghuang species might not be exclusive to a few categories [ 32 , 101 ]. Some changes of the solvent might occur in some research papers, such as replacing ethanol with 70% methanol or absolute alcohol [ 9 , 25 , 28 ].…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Sanghuang was also mentioned in the Compendium of Materia Medica in the Ming Dynasty as a traditional medicinal mushroom taken orally to eliminate the body’s toxins [ 2 , 21 ]. Entering modern times, pharmaceutical research has demonstrated multiple functions of Sanghuangporus spp., including the ability to improve blood circulation, scavenge free radicals, demonstrate anti-inflammatory effects, anti-carcinogenesis, antioxidative abilities, immunomodulatory effects, antidiabetic activities, antimicrobial abilities, and antiaging effects [ 2 , 4 , 9 , 14 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 ]. Some research has also provided evidence of antigout, sleep-improving, neuroprotective, and hepatoprotective activities [ 3 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rutin is a polyphenolic flavonoid with anti-inflammatory and antioxidant properties and is of significant medical importance [ 24 ]. The quantitative analysis of active ingredients in Sanghuangporus is crucial for evaluating its quality, and identifying antioxidants from it can enhance the accuracy of product quality assessment [ 25 ]. Therefore, searching for potential biomarkers in flavonoids may become a crucial criterion for evaluating the efficacy of Sanghuangporus therapy.…”
Section: Introductionmentioning
confidence: 99%